Accounting-based asset return smoothing in participating life annuities: Implications for annuitants, insurers, and policymakers - Raimond Maurer; Olivia S. Mitchell; Ralph Rogalla; Ivonne Siegelin (Goethe University Frankfurt, Center for Financial Studies (CFS), 2015)
This chapter outlines the conditions under which accounting-based smoothing can be beneficial for policyholders who hold with-profit or participating payout life annuities (PLAs). We use a realistically-calibrated model of PLAs to explore how alternative accounting techniques influence policyholder welfare as well as insurer profitability and stability. We find that accounting smoothing of participating life annuities is favorable to consumers and insurers, as it mitigates the impact of short-term volatility and enhances the utility of these long-term annuity contracts.
urn:nbn:de:hebis:30:3-382887
Keywords: 330